Equivalents of Vedic Puraṁ-Dará- in Baltic Tradition: the Mythic Nature of Image - Razauskas, Dainius (Acta Orientalia Vilnensia, 2001)
As is well known, Vedic thundergod Indra used to “break citadels (pur)”, therefore he was given a nickname puraṁdará- ‘the citadel-breaker’. This epithet is by some scholars connected with the downfall of such Hindu valley cities as, for example, Harapa, and ascribed to the invading Arian image. The others have criticised such a view on different grounds, one of which consists of the fact that the concept puraṁdará- deals not with historical material altogether but with the mythological one (and if it has some historical links at all, these might be only secondary projections of the mythological content). For example, the Lithuanian (and Lettish too) folk tradition presents some motives of the thundergod Perkūnas breaking the pilis ‘castle’ of his antagonist Velnias, whose habit to construct stone ramparts and dams is well known. As is also well known, Lith.pilis (and Lett. pils too) is the precise etymological equivalent of the Vedic pur- (cf. purí-); and, furthermore, the name of the mentioned antagonist of Lithuanian thundergod, that is Velnias (var. Velas), according to Russian scholars V. Ivanov and V. Toporov, is etymologically connected with the name of the Vedic thundergod Indra’s antagonist Vala-, meaning ‘rock’, which in Lithuanian again corresponds to uolá (lE *u̯el-). Moreover, Lith. uolá (cf. Lett. valnis ‘rampart’ from the same IE *u̯el-) can also indicate a ‘rampart’, or ‘wall of stones’ (cf. Lith.pýlimas ‘rampart’ : pilís), which, in its turn, corresponds to the primary meaning of the Vedic pur- (according to O. Schrader, W Rau etc.). Thus the epithet puraṁdará- becomes included into the main stream of Vedic images of Indra destroying Vala and, on a wider horizon, into the context of the so called “principal myth”. Furthermore, Lith. uolá has also the meaning of ‘hardened soil’ or ‘petrified ground’, and in RV IV.28.5, due to the Indra’s victory over his enemy and the destruction of their stone enclosures, “the earth opens”. Lithuanian Perkūnas (or his later substitutes), in his turn, as the first thunder in spring, used to “open the earth” for vegetation to sprout out. And the verb Lith. ati-daryti ‘open’, according to one of the main etymologies, is connected with Lith. dirti ‘flay, flog, thrash’ (cf. dirva ‘soil, field, arable land’) and, finally, with Vedic drṇanti ‘bursts, causes to burst, tears’ (ct. drti- ‘skin of leather’, dara- ‘hole in the ground, cave’ etc.), to which the second part of the composition puraṁ-dará- derives. Therefore, in different (though interconnected) mythological contexts, the Lithuanian equivalents to both parts of the Vedic compound noun puraṁ-dará- have be’en found, thus, by the way, altogether removing the ground for its historical interpretation.